2021
DOI: 10.1007/s10884-021-10050-0
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Well-Posedness Result for the Modified KdV Equation in the Fourier–Lebesgue Spaces

Abstract: We study the well-posedness of the complex-valued modified Korteweg-de Vries equation (mKdV) on the circle at low regularity. In our previous work (2021), we introduced the second renormalized mKdV equation, based on the conservation of momentum, which we proposed as the correct model to study the complex-valued mKdV outside $$H^\frac{1}{2}({\mathbb {T}})$$ H 1 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…In the context of nonlinear Schrödinger type equations, such instability results without renormalization in negative Sobolev spaces are known even deterministically; see [30,49]. See also [16,17] for a similar instability result on the complex-valued mKdV equation in the deterministic setting.…”
Section: Annales De L'institut Fouriermentioning
confidence: 96%
See 1 more Smart Citation
“…In the context of nonlinear Schrödinger type equations, such instability results without renormalization in negative Sobolev spaces are known even deterministically; see [30,49]. See also [16,17] for a similar instability result on the complex-valued mKdV equation in the deterministic setting.…”
Section: Annales De L'institut Fouriermentioning
confidence: 96%
“…for k ∈ N, where the positive constant c is independent of k and N . Noting that the right-hand side is summable in N ∈ N, we can invoke the Borel-Cantelli lemma to conclude that there exists Ω k of full probability such that (16) for each ω ∈ Ω k , there exists M = M (ω) 1 such that for any N M , we have…”
Section: Annales De L'institut Fouriermentioning
confidence: 99%
“…This shows that the unrenormalized equation is ill-posed in Fourier Lebesgue spaces of negative Sobolev regularity. Further recent local well-posedness results on the complex-valued mKdV equation in Fourier Lebesgue spaces are due to Chapouto [10,11]. We also mention the recent work of Forlano [19], who unified and simplified previous proofs of global well-posedness for the modified Korteweg-de Vries equation in Sobolev spaces H s (K) with 0 ≤ s < ε N ε f L 2 (T) , I have proved in [38] that there is no data-to-solution mapping to the unrenormalized equation in the following sense in H s (T) for s < 0: A map S : H s (T) → C([−T, T ], H s (T)) where T = T ( u 0 H s ) > 0 is referred to as data-to-solution mapping to (81) if it satisfies the following properties:…”
Section: Strichartz Estimates On Frequency Dependent Time Intervalsmentioning
confidence: 99%
“…We emphasize that the decoupling arguments do not distinguish between the square and irrational tori, which means we can allow for general T 2 γ . We suppose that for i = 1, 2, 3 (11) supp( fi ) ⊆ B(ξ * i , N 3 ) for some ξ * i ∈ B(0, 2N 1 ) and (12) |ξ * 1 − ξ * 2 | N 1 . Consider the expression (13) [0,N −α 1 ]×T 2 γ |e it∆ f 1 e it∆ f 2 e it∆ f 3 | 4/3 dxdt.…”
Section: Introductionmentioning
confidence: 99%
“…To understand why this is the case, we recall that Chapouto [6,7] showed that (1.9) and even its renormalized variant, in the sense of the corresponding gauge transformation to (1.8), are ill-posed below H 1/2 (T). The cause of the instability is the possibility that the momentum P (q) = Im ˆT qq ′ dx may be infinite outside H 1/2 (T).…”
Section: Introductionmentioning
confidence: 99%